Securing rights in the twenty-first century: A comparison of the disability and older persons' rights conventions. Issue 4 (1st October 2016) - Sciubba, Jennifer Dabbs
ABSTRACT: This article assesses the outcome of the proposed UN Convention on the Rights of Older People (CROP) by comparing its political, economic, and social contexts with those of the 2006 Convention on the Rights of Persons with Disabilities (CRPD). The research draws on interviews with those involved in the debates, nonparticipant observation, and analysis of primary and secondary literature. The article concludes that weakness of the aging advocacy network compared to the disability network and a relatively more closed political opportunity structure negatively influence the CROP's prospects. However, many of the hurdles proponents of the CROP face are similar to those faced at the beginning of the CRPD campaign, so progress and eventual adoption are possible. By comparison with the closely related CRPD, social scientists can better understand the institutional and contextual factors that influence campaign success in the contemporary context and advocates of the CROP can better anticipate roadblocks.